Knowledge, attittudes and practices of healthcare professionals towards adverse drug reaction reporting in Mafikeng Provincial Hospital - Segomotso, Nametso Patience (University of Limpopo ( Medunsa Campus), 2011)
Abstract Background: Prevention, monitoring and reporting of adverse drug reactions is still a challenge among healthcare professionals. Even though some adverse drug reactions are minor and can be resolved quickly some can cause permanent disability or death. A recent South African study in a secondary hospital found that 6.3% of medical admissions were due to adverse drug reactions, which is similar to proportions found in developed countries. It is the responsibility of the healthcare professionals to detect, investigate, manage and report adverse drug reactions. Aim of the study: This study aimed to determine knowledge, attitudes and practices of healthcare professionals (doctors, nurses and pharmacists) regarding the reporting of patients‟ adverse drug reaction at Mafikeng Provincial Hospital. Methods: This was a descriptive quantitative study. A questionnaire was used to collect data from 29 doctors, 88 nurses and 5 pharmacists. Data was collected on demographic characteristics of the healthcare professionals, their knowledge, attitudes and practices towards ADR reporting. Data analysis was conducted using STATA (version 11) and Epi info (version 6). A test of association of selected variables was done using Pearson chi–square and logistic analysis to measure the association. Results: More than half of the participants were male (56.3%) and 53.8% percent of them were younger than 40 years. Majority of the respondents (72.27%) indicated that they do not know how to report ADRs. There was no significant difference in terms of knowledge by age category. None of the healthcare professionals have ever sent their ADR forms to the pharmacovigilance centre. Ninety-one percent (91.53%) felt that reporting of ADR can benefit the public health, 78.63% felt that filling of the ADR yellow form is useful and 98.29% felt that ADR should be compulsory. There was no significant association between knowledge of how to report and attitude towards reporting (X²=1.0, p= 0.317), no association between knowledge and practice (X²=0.974, p= 0.324). iv Conclusions: This study revealed that more than a third of the respondents (72.29%) did not have the knowledge of the procedure for reporting ADRs. Healthcare professionals had a positive attitude towards ADR; 98.29% of them said that ADR reporting should be compulsory. There was no significant association between knowledge, attitude and practice toward ADR reporting. Healthcare professionals' knowledge can be improved through educational interventions and trainings.
Thesis (MPH)--University of Limpopo, 2011.